Plánování rozvoje cyklistické infrastruktury s využitím metod podpory prostorového rozhodování - Ruda, Aleš; Floková, Ludmila (Univerzita Pardubice, 2017)
Planning the development of cycling infrastructure underlines the importance of suitable and sustainable transportation inside cities. In spite that decision making process implements many statistical tools, proposing new cycle paths is based on both quantitative evaluating and qualitative respecting strategic intent of the city. The main goal of the paper is to extend currently accepted approaches in modelling of cycling infrastructure towards geostatistical analysis. The research documents a comparative study of different interpolation techniques producing raster surfaces for further processing using multicriterial evaluation. To choose an appropriate interpolation method several methods were tested, especially Inverse Distance Weighted, Radial Base Function, Simple Kriging, Ordinary Kriging and Empirical Bayesian Kriging. Besides interpolated data taken from field counting, points of cyclists´ interest have been implemented into the assessment. Considering two strategies (safety and preparedness for cycling infrastructure development) determining weights, two sets of proposals have been also presented. The results were equally reclassified into five classes for possible comparison.
Planning the development of cycling infrastructure using spatial decision making support methods
Keywords: cycle paths; geostatistical interpolation; cyclists; multicriterial evaluation; infrastructure planning; C15; C88; R41